Initial Hyperleukocytosis and Neutrophilia in Nasopharyngeal Carcinoma: Incidence and Prognostic Impact. - Zhen Su; Yan-Ping Mao; Pu-Yun OuYang; Jie Tang; Fang-Yun Xie (PLoS ONE, 2015)
BACKGROUND:This study aimed to evaluate initial hyperleukocytosis and neutrophilia as prognostic indicators in patients with nasopharyngeal carcinoma. METHODS:A retrospective analysis of 5,854 patients identified from a cohort of 6,035 patients diagnosed with nasopharyngeal carcinoma was performed with initial hyperleukocytosis and neutrophilia analyzed as prognostic factors. Multivariate Cox proportional hazards analyses were applied. RESULTS:Hyperleukocytosis was observed in 508 patients (8.7%). Multivariate analysis showed that initial hyperleukocytosis was an independent predictor of death (HR 1.40, 95%CI 1.15-1.70, p = 0.001), progression (HR 1.25, 95%CI 1.06-1.47, p = 0.007) and, marginally, distant metastasis (HR 1.21, 95%CI 0.97-1.52, p = 0.088). Neutrophilia was also an independent predictor of death (HR 1.46, 95%CI 1.18-1.81, p = 0.001), progression (HR 1.31, 95%CI 1.10-1.56, p = 0.003), and distant metastasis (HR 1.29, 95%CI 1.02-1.65, p = 0.036), after adjusting for prognostic factors and excluding hyperleukocytosis. CONCLUSION:Initial hyperleukocytosis and neutrophilia were independent, poor prognostic factors and may be convenient and useful biological markers for survival of patients with nasopharyngeal carcinoma.